Functional effects of ice plant amylases on cake and bun quality. (June 2019) - Khemakhem, Bassem; El Abed, Hanen; Chakroun, Mouna; Fendri, Imen; Smaoui, Slim
Abstract: Amylases were extracted from the ice plant ( Mesembryanthemum crystallinum L.) and their effect on cake and bun qualities was studied. The amylolytic activity showed a good stability over a wide pH ranging from 2 to 10 with two pH optima: the first at pH 5 (Amy A) and the second at pH 8 (Amy B). This suggests that there are two amylases in M. crystallinum extracts. HPLC analysis of the hydrolysis products showed that these enzymes predominantly formed maltose and glucose. The extract containing AmyA and AmyB might be potentially beneficial to the baking industry. The incorporation of a M. crystallinum extract into cake and bun formulations was evaluated. Four different concentrations of the amylase extracts were used. At 0.01 and 2.76 × 10 −3 U/g, respectively, for cakes and buns, a significant (P<0.05) decrease in water absorption, bulk density, microstructural characteristics and instrumentally color parameters (L*, a* and b*) were observed. Texture was evaluated instrumentally using the texture profile analysis with cakes and buns. An increase of textural properties (hardness, springiness and cohesion) for formulated products was observed. Sensory evaluation confirmed that the sensory scores for both cakes and buns were improved. Correlations between overall acceptability and sensory characteristics were observed. Given these results, these amylases from ice plant could be considered for use in baking formulations.